Digital rhetoric and global literacies communication modes and digital practices in the networked world - Verhulsdonck, Gustav 1975-; Limbu, Marohang 1965- (Advances in linguistics and communication studies (ALCS) book series, 2014)
"This book compiles relevant theoretical frameworks, current practical applications, and emerging practices of digital rhetoric, highlighting the key principles and understandings of the underlying modes, practices, and literacies of communication"..